An analysis of the costs and performance of vehicles fueled by alternative energy carriers - Lynch, Alexander, author; Bradley, Thomas, advisor; Coburn, Tim, committee member; Olsen, Daniel B., committee member (Colorado State University. Libraries, 2024)
The transportation sector stands at the crossroads of new challenges and opportunities, driven by the pressing need to mitigate environmental impacts, enhance energy efficiency, and ensure sustainable mobility solutions. This transition will occur across diverse transportation modes, each with distinct characteristics and challenges. From light duty vehicles embracing electrification to maritime transport adopting alternative fuel engines, the push for low-carbon technology is reshaping the landscape of transportation. In this context, it is necessary to conduct a review and assessment of technologies, environmental benefits, and costs of alternative fuels and powertrains across a broad set of applications in the transportation sector. This study seeks to perform this assessment by combining bottom-up cost analysis, environmental assessments, and reviews of the literature to examine the techno-economic aspects of various fuel and powertrain options in the transportation sector. This approach involves detailed evaluations of individual components and systems to model the cost structures and efficiency profiles of vehicles. The results illustrated in this thesis will be embedded into adoption models to enable governments, utilities, private fleets, and other shareholders to make informed transportation planning decisions.
Zip file contains data spreadsheets.